THE CONCEPT OF REPENTANCE IN THE STORY OF PROPHET YUNUS AND ITS IMPLICATIONS FOR HUMAN CHARACTER FORMATION IN THE QUR'AN - Muhamad Shofwan Muttaqin; Ahmad Suharto; Fahmi Akhyar Al Farabi; Khilya Az-Zahra; Ali Mahfuz Munawwar (JOURNAL OF QUR'AN AND HADITH STUDIES, 2026)
This study examines the concept of repentance (tawbah) in the story of Prophet Yunus (Jonah) and its implications for human character formation from a Qurʾānic perspective. The research is motivated by the increasing moral, spiritual, and psychological challenges of contemporary society. According to the World Health Organization, nearly one in seven people worldwide experienced mental disorders in 2021, indicating the need for approaches that integrate spiritual and psychological well-being. The story of Prophet Yunus contains educational and spiritual values that are relevant to self-reformation and character development. This study employs a qualitative library research approach using thematic Qurʾānic exegesis (tafsīr mawḍū‘ī). Data were collected from Qurʾānic verses related to the story of Prophet Yunus and analyzed through classical and contemporary tafsir literature. The findings reveal five essential dimensions of repentance: remorse, self-improvement, patience, glorification of Allah through tasbih, and seeking Allah’s help. These dimensions contribute to the development of positive character traits, including humility, wisdom, self-confidence, emotional balance, and optimism. The study further argues that repentance functions not only as a theological doctrine but also as a transformative spiritual practice that supports moral development and psychological well-being. Consistent with insights from the psychology of religion, repentance may serve as a form of spiritual self-reformation that enhances emotional regulation and resilience. Therefore, the story of Prophet Yunus offers a Qurʾānic framework for character formation grounded in Islamic spirituality and relevant to addressing contemporary moral and psychological challenges.